Screening instruments for eating disorders in pregnancy: Current evidence, challenges, and future directions. Issue 9 (18th July 2022) - Dörsam, Annica Franziska; Bye, Amanda; Graf, Johanna; Howard, Louise M.; Throm, Jana Katharina; Müller, Mitho; Wallwiener, Stephanie; Zipfel, Stephan; Micali, Nadia; Giel, Katrin Elisabeth
Abstract: Pregnancy is a vulnerable period for eating disorder (ED) occurrence and maternal EDs are associated with heightened risk of adverse pregnancy and infant outcomes. This highlights the need to identify pregnant women with past or current EDs in order to offer appropriate support. However, there is a knowledge and practice gap on screening pregnant women for EDs. Clinical guidance is lacking in international treatment guidelines, which is unsurprising given that no validated ED screening tool specifically designed for use in antenatal populations exists. Moreover, data on the effectiveness of general population screening tools for identifying EDs in pregnant women are scarce. This article provides a synthesis of current evidence, treatment guidelines, and data on the diagnostic accuracy for screening for EDs in antenatal samples from three studies with different screening approaches. We outline recommendations for future steps to tackle the knowledge and practice gap on screening for EDs in pregnant women, including next steps for the development of a pregnancy‐specific ED screener and the use of general mental health screeners to detect EDs during pregnancy. Up‐to‐date, the jury is still out as how to best identify current or past EDs in pregnancy. More research is needed to assess the efficacy of using general mental health screeners versus ED‐specific screening instruments to detect ED in pregnancy. Additionally, clinicians have to be trained on how to assess and manage EDs during pregnancy. Public Significance: Identifying pregnant women with eating disorders (EDs) is a public health concern which can be addressed using multiple approaches, including implementation of general and specific assessments within routine antenatal care, and training of healthcare professionals.